Study the activity of conjugated antimicrobial peptide WW-185 against clinically important bacteria - Ali H. Salama (Pensoft Publishers, 2023)
Multidrug-resistance bacteria are a serious problem for health specialists and all the people in the world. The main reasons for this problem are the misuse of antibiotics and the limited number of antibiotics as compared to the different human diseases. Important antibiotic-resistant bacteria include Methicillin-resistant Staphylococcus aureus (MRSA) and Extended-Spectrum β-Lactamases E. coli (ESBL E. coli), These two types of bacteria can cause life-threatening diseases and poses a big problem in choosing suitable antibiotics for infections caused by them. Antimicrobial peptides (AMPs) are considered promising antimicrobial agents that meet the required criteria for novel antimicrobial drugs. This study aims to design novel and safe AMP to be used as antimicrobial agents. In this study, an unique modified AMPs called WW-158 was designed to have a hydrophilic and hydrophobic balance using arginine to represent the cationic part and tryptophan to show the hydrophobic part. It showed good activity against MRSA with a MIC value of 35 μM. These effective concentrations were associated with negligible toxicity toward human red blood cells. Furthermore, our results showed that most of the combined groups of peptides with eight conventional antibiotics displayed synergistic modes of action or additive effects.